Aphid herbivory on macrophytes drives adaptive evolution in an aquatic community via indirect effects - Martin Schäfer; Antonino Malacrinò; Christoph Walcher; Piet Spaak; Marie Serwaty-Sárazová; Silvana Käser; Thea Bulas; Christine Dambone-Bösch; Eric Dexter; Jürgen Hottinger; Laura Böttner; Christoph Vorburger; et al. (Proceedings of the National Academy of Sciences, 2025)
Indirect ecological effects occur when the impact of one species on another is mediated by a third species or the shared environment. Although indirect effects are ubiquitous in nature, we know remarkably little about how they may drive ecoevolutionary processes across community boundaries. Here, we show that insect (aphid) herbivory on macrophytes (duckweed) drove the adaptive evolution of a planktonic crustacean ( Daphnia magna ) in large outdoor aquatic mesocosms via indirect ecological effects. Aphid herbivory reduced duckweed growth and increased the nutrient and light availability in the water column, which promoted phytoplankton growth and boosted the abundance of D. magna that feed on phytoplankton. Whole-genome pool-sequencing and phenotypic assays revealed aphid-herbivory-mediated evolutionary changes to Daphnia population. Transplant experiments indicated that these evolutionary changes were adaptive. Furthermore, aphid-herbivory-mediated biotic and abiotic changes in the aquatic community increased the performance of the macrophytes and aphids. These results demonstrate that indirect ecological effects can shape ecoevolutionary interactions between seemingly independent species in natural communities.